2013
DOI: 10.1017/s1751731112002042
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of cross-bred cows for organic farms based on cross-breeding effects on production and functional traits

Abstract: Data from 113 Dutch organic farms were analysed to determine the effect of cross-breeding on production and functional traits. In total, data on 33 788 lactations between January 2003 and February 2009 from 15 015 cows were available. Holstein-Friesian pure-bred cows produced most kg of milk in 305 days, but with the lowest percentages of fat and protein of all pure-bred cows in the data set. Cross-breeding Holstein dairy cows with other breeds (Brown Swiss, Dutch Friesian, Groningen White Headed, Jersey, Meus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 43 publications
1
21
0
3
Order By: Relevance
“…The small estimates of heterosis and recombination loss effects for contents could be related to the high heritability of these traits. De Haas et al (2013) and Freyer et al (2008) found similar results. The higher estimates of crossbreeding parameters on fat content in the HO × MO population might be related to the large heterosis effect estimated for fat yield in this population.…”
supporting
confidence: 57%
“…The small estimates of heterosis and recombination loss effects for contents could be related to the high heritability of these traits. De Haas et al (2013) and Freyer et al (2008) found similar results. The higher estimates of crossbreeding parameters on fat content in the HO × MO population might be related to the large heterosis effect estimated for fat yield in this population.…”
supporting
confidence: 57%
“…Availability of high throughput marker data contributes to an efficient selection of individuals with low inbreeding coefficients, but for controlling inbreeding in a long-term perspective, genomic relationships among selection candidates should be used in mating designs that are specified by breeding organizations. In addition to those concerns, the evaluation criterion 'inbreeding' is less meaningful, especially when applying cross-breeding strategies in organic farming systems (de Haas et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Swalve () compared pure‐bred Holstein‐Friesian and their crosses with Brown Swiss and Swedish Red reared on farms in Germany and observed a significantly higher number of services per conception in Holstein‐Friesian cows. In a study carried out in the Netherlands, in which the suitability of cross‐bred animals for organic systems was analysed, the calving interval was longest in pure Holstein‐Friesian and shortest in pure‐bred Fleckvieh (Haas, Smolders, Hoorneman, Nauta, & Veerkamp, ). Finally, in a study conducted in Austria under Alpine conditions, Holstein‐Friesian cows (selected for superior lifetime performance and fertility) were found to be reproductively more efficient than Brown Swiss, although the Brown Swiss were also more productive (Horn et al, ).…”
Section: Discussionmentioning
confidence: 99%